Faktor-Faktor yang Memengaruhi Minat Penabung terhadap Tabungan Mudharobah (TABAH) di BMT NU Cabang Weringin Bondowoso - Sairosi, Imam; Nuntupa, Nuntupa; Yuana, Anik Gita (MES Management Journal, 2024)
This study aims to analyze the factors influencing savers' interest in Mudharabah Savings (TABAH) at BMT NU Branch Wringin Bondowoso. A quantitative approach was employed in this research involving 45 respondents who are customers of BMT NU Branch Wringin Bondowoso. Data were collected through online and direct distribution of questionnaires to savers. Data analysis was conducted using multiple regression to test the relationship between independent variables (trust, risk perception, profit, promotion, and external factors) and the dependent variable (savers' interest in TABAH). The research findings indicate that trust (β = 0.324, p < 0.001), risk perception (β = -0.211, p < 0.05), and external factors (β = 0.178, p < 0.05) have a significant influence on savers' interest in TABAH, while profit (β = 0.097, p > 0.05) and promotion (β = 0.065, p > 0.05) do not have a significant influence. The practical implications of these findings underscore the importance of strengthening trust and reducing savers' risk perceptions towards TABAH through effective marketing strategies and service enhancements. This study provides valuable insights for the management of BMT NU Branch Wringin Bondowoso in enhancing savers' interest in Mudharabah savings products.